(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Currently, no one denies the need to introduce a computer into the educational process. But computer-assisted learning can exceed the effectiveness of the machine-less method of teaching only when the computer does not act as a simple addition to the traditionally established methods of teaching, but when its use is associated with the restructuring of the structural components of the educational process.